Patient preparation for bariatric surgery - Benotti, Peter N. (Springer New York, 2014)
Patient Preparation for Bariatric Surgery provides a comprehensive and state of the art review of all aspects of the patient preparation process, The text reviews current literature and controversies involving sources of referrals and the difficulties encountered by primary care physicians in managing patients with extreme obesity. Strategies for addressing this problem and integrating primary care physicians in comprehensive obesity programs are presented. The text also reviews current indications for surgery and the current patient access limitations that have resulted in the need for revised surgical indications based more on medical need than mere extent of obesity. Written by an authority in the field, Patient Preparation for Bariatric Surgery is a valuable resource for bariatric surgeons, bariatric physicians and all allied health personnel who manage patients with extreme obesity and will assist in the advancement of this area of surgery as well as stimulate new discovery.